An Analysation of Tourists' Behavior and Online Source Credibility in Kanchanaburi Province, Thailand - Chitlada Pinthong (2020)
© 2020 IEEE. Social media has become an important communication platform for people to share their opinions, to search information, services or products and to read and write online reviews. This study aims to investigate the purchase decision processes of tourists who travel to Kanchanaburi province and credibility of online reviews in social media sites. Also, the relationship between tourist's purchase decision process and the credibility of online reviews in social media sites was examined. The results indicate that the relationships between the process of tourist decision-making behavior and credibility of reviews in social media sites are a positively significant correlation.